Truncation of CXCL8 to CXCL8(9‐77) enhances actin polymerization and in vivo migration of neutrophils. Issue 6 (9th April 2020) - Metzemaekers, Mieke; Vandendriessche, Sofie; Berghmans, Nele; Gouwy, Mieke; Proost, Paul
Abstract: CXCL8 is the principal human neutrophil‐attracting chemokine and a major mediator of inflammation. The chemokine exerts its neutrophil‐chemotactic and neutrophil‐activating activities via interaction with glycosaminoglycans (GAGs) and activation of the G protein‐coupled receptors (GPCRs) CXCR1 and CXCR2. Natural CXCL8 displays an exceptional degree of amino (NH2 )‐terminal heterogeneity. Most CXCL8 forms result from proteolytic processing of authentic CXCL8(1‐77). Here, we compared the potencies to activate and recruit neutrophils of the 3 most abundant natural CXCL8 forms: full‐length 77 amino acid CXCL8 and the 2 major natural truncated forms lacking 5 or 8 NH2 ‐terminal amino acids. NH2 ‐terminal truncation hardly affected the capacity of CXCL8 to induce shedding of CD62L or to up‐regulate the expression of the adhesion molecules CD11a, CD11b, or CD15 on human neutrophils. In addition, the potency of CXCL8 to induce neutrophil degranulation and its effect on phagocytosis remained unaltered upon removal of 5 or 8 NH2 ‐terminal residues. However, NH2 ‐terminal truncation strongly potentiated CXCL8‐induced actin polymerization. CXCL8(6‐77) and CXCL8(9‐77) showed a comparable capacity to induce Ca 2+ signaling in human neutrophils and to direct in vitro neutrophil migration. Strikingly, the ability of CXCL8(9‐77) to recruit neutrophils into the peritoneal cavity of mice was significantly enhanced compared to CXCL8(6‐77). These results suggest that NH2 ‐terminal truncation influences specific biological activities of CXCL8 and indicate that CXCL8(9‐77) may be the most potent neutrophil‐attracting CXCL8 form in vivo. Abstract : Natural NH2 ‐terminal truncation potentiates CXCL8‐induced actin polymerization and neutrophil recruitment in vivo but has no major impact on adhesion molecule expression or neutrophil degranulation.